Compartmentalization in PVC super-phylum: evolution and impact - Pinos, Sandrine (Biol Direct, 2016)
BACKGROUND: The PVC super-phylum gathers bacteria from seven phyla (Planctomycetes, Verrucomicrobiae, Chlamydiae, Lentisphaera, Poribacteria, OP3, WWE2) presenting different lifestyles, cell plans and environments. Planctomyces and several Verrucomicrobiae exhibit a complex cell plan, with an intracytoplasmic membrane inducing the compartmentalization of the cytoplasm into two regions (pirellulosome and paryphoplasm). The evolution and function of this cell plan is still subject to debate. In this work, we hypothesized that it could play a role in protection of the bacterial DNA, especially against Horizontal Genes Transfers (HGT). Therefore, 64 bacterial genomes belonging to seven different phyla (whose four PVC phyla) were studied. We reconstructed the evolution of the cell plan as precisely as possible, thanks to information obtained by bibliographic study and electronic microscopy. We used a strategy based on comparative phylogenomic in order to determine the part occupied by the horizontal transfers for each studied genomes. RESULTS: Our results show that the bacteria Simkania negevensis (Chlamydiae) and Coraliomargarita akajimensis (Verrucomicrobiae), whose cell plan were unknown before, are compartmentalized, as we can see on the micrographies. This is one of the first indication of the presence of an intracytoplasmic membrane in a Chlamydiae. The proportion of HGT does not seems to be related to the cell plan of bacteria, suggesting that compartmentalization does not induce a protection of bacterial DNA against HGT. Conversely, lifestyle of bacteria seems to impact the ability of bacteria to exchange genes. CONCLUSIONS: Our study allows a best reconstruction of the evolution of intracytoplasmic membrane, but this structure seems to have no impact on HGT occurrences. REVIEWERS: This article was reviewed by Mircea Podar and Olivier Tenaillon. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13062-016-0144-3) contains supplementary material, which is available to authorized users.